Hypusine Modification of the Ribosome-binding Protein eIF5A, a Target for New Anti-Inflammatory Drugs: Understanding the Action of the Inhibitor GC7 on a Murine Macrophage Cell Line - Almeida, Oedem Paulo de [UNESP]; Toledo, Thais Regina [UNESP]; Rossi, Danuza [UNESP]; Rossetto, Daniella de Barros [UNESP]; Watanabe, Tatiana Faria [UNESP]; Galvao, Fabio Carrilho [UNESP]; Medeiros, Alexandra Ivo de [UNESP]; Zanelli, Cleslei Fernando [UNESP]; Valentini, Sandro Roberto [UNESP] (Bentham Science Publ Ltd, 2014)
Inflammation is part of an important mechanism triggered by the innate immune response that rapidly responds to invading microorganisms and tissue injury. One important elicitor of the inflammatory response is the Gram-negative bacteria component lipopolysaccharide (LPS), which induces the activation of innate immune response cells, the release of proinflammatory cytokines, such as interleukin 1 and tumor necrosis factor alpha (TNF-alpha), and the cellular generation of nitric oxide (NO) by the inducible nitric oxide synthase (iNOS). Although essential to the immune response, uncontrolled inflammatory responses can lead to pathological conditions, such as sepsis and rheumatoid arthritis. Therefore, identifying cellular targets for new anti-inflammatory treatments is crucial to improving therapeutic control of inflammation-related diseases. More recently, the translation factor eIF5A has been demonstrated to have a proinflammatory role in the release of cytokines and the production of NO. As eIF5A requires and essential and unique modification of a specific residue of lysine, changing it to hypusine, eIF5A is an interesting cellular target for anti-inflammatory treatment. The present study reviews the literature concerning the anti-inflammatory effects of inhibiting eIF5A function. We also present new data showing that the inhibition of eIF5A function by the small molecule GC7 significantly decreases TNF-alpha release without affecting TNF-alpha mRNA levels. We discuss the mechanisms by which eIF5A may interfere with TNF-alpha mRNA translation by binding to and regulating the function of ribosomes during protein synthesis.
Keywords: eIF5A; hypusine modification inhibitor; CG7; TNF-alpha; anti-inflammatory drugs